The Influence of Products and Places on Consumer Purchase Decisions at PT. Utomo Prosperous with Grago, Kaur Regency - Derry Aprido Yarangga; Siswanto; Meiffa Herfianti (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the effect of the product and place toward consumer purchasing decisions at PT. Utomo Sejahtera Bersama Grago of Kaur Regency. The sample in this study 70 customers who purchase shrimp at PT. Utomo Sejahtera Bersama Grago of Kaur Regency. Data collection used questionnaires and the analysis method used was multiple linear regression, determinative test and hypothesis testing. The results of the regression analysis show Y = 2,427 + 0,501X1 + 0,390 X2, this illustrates the positive regression direction. This means that if the product and place are considered equal to zero then the purchasing decision variable will remain at 2,427. The positive regression direction illustrates that as product quality increases, purchasing decisions will also increase and the more strategic the place, the purchasing decisions will also increase. The magnitude of the coefficient of determination is 0.678. This means that X1 (product) and X2 (place) influence the purchasing decision (Y) of 67.8% while the rest (100% -67.8%) of 32.2% is influenced by other variables not examined in this research. T test results for product variables (X1) have a significant value of 0,000 and place variables (X2) have a significant value of 0,000. Because the significant value of each variable is smaller than 0.05, it can be concluded the product and place variables have a significant effect partially on the consumer purchasing decision variables at PT. Utomo Sejahtera Bersama Grago of Kaur Regency. F test results at a significance level of 0.05 explain that product and place variables have a significant effect simultaneously on consumer purchasing decisions at PT. Utomo Sejahtera Bersama Grago of Kaur Regency.